Are patients living far from hospital at higher risk of late adjuvant chemotherapy for colon cancer?. Issue 8 (22nd March 2022) - Vermeulin, Thomas; Lahbib, Hana; Lucas, Mélodie; Czernichow, Pierre; Jusot, Florence; Di Fiore, Frédéric; Merle, Véronique
Abstract : Aims: Late adjuvant chemotherapy (aCT) administration after colectomy (>56 d) is known to be associated with impaired prognosis. We aim to identify risk factors associated with late aCT, especially the travel time between patients' home and hospital. Methods: We performed a retrospective monocentre cohort study. Patients included had a colectomy for a stage III or high risk stage II colon cancer between 2009 and 2015 performed at a French university hospital. Risk factors for late aCT were identified using a fractional polynomial logistic regression. Results: Ninety‐four patients were included. The risk of late aCT was associated with travel time length, emergent colectomy, the need for scheduled care before aCT, and length of time between colectomy and postoperative multidisciplinary meeting advising aCT. Conclusion: Our study suggests that, in patients with colon cancer, factors unrelated to disease severity and complexity could be associated with a higher risk of late aCT.